Fruit Calcium: Transport and Physiology - Hocking, Bradleigh; Tyerman, Stephen D.; Burton, Rachel A.; Gilliham, Matthew (Frontiers in Plant Science, 2016)
Calcium has well-documented roles in plant signaling, water relations and cell wall interactions. Significant research into how calcium impacts these individual processes in various tissues has been carried out; however, the influence of calcium on fruit ripening has not been thoroughly explored. Here, we review the current state of knowledge on how calcium may impact fruit development, physical traits and disease susceptibility through facilitating developmental and stress response signaling, stabilizing membranes, influencing water relations and modifying cell wall properties through cross-linking of de-esterified pectins. We explore the involvement of calcium in hormone signaling integral to ripening and the physiological mechanisms behind common disorders that have been associated with fruit calcium deficiency (e.g. blossom end rot in tomatoes or bitter pit in apples). This review works towards an improved understanding of how the many roles of calcium interact to influence fruit ripening, and proposes future research directions to fill knowledge gaps. Specifically, we focus mostly on grapes and present a model that integrates existing knowledge around these various functions of calcium in fruit, which provides a basis for understanding the physiological impacts of sub-optimal calcium nutrition in grapes. Calcium accumulation and distribution in fruit is shown to be highly dependent on water delivery and cell wall interactions in the apoplasm. Localized calcium deficiencies observed in particular species or varieties can result from differences in xylem morphology, fruit water relations and pectin composition, and can cause leaky membranes, irregular cell wall softening, impaired hormonal signaling and aberrant fruit development. We propose that the role of apoplasmic calcium-pectin crosslinking, particularly in the xylem, is an understudied area that may have a key influence on fruit water relations. Furthermore, we believe that improved knowledge of the calcium-regulated signaling pathways that control ripening would assist in addressing calcium deficiency disorders and improving fruit pathogen resistance.